(untitled) (Revista Nacional de Odontología, 2021)
During the stomatological consultation one of the most frequent conditions is toothache, commonly known as "dental pain or toothache". Its intensity forces the patient to attend immediately. This alteration, due to its magnitude, reduces the capacity and performance of many people. The sensation of dental pain originates in the receptors located in the pulp that contain nerve fibers. Cement and enamel are insensitive due to the lack of said cells, thanks to which dentin pain is identified, which is intense and lasts a few seconds, which is caused by external agents (hot or cold drinks, acids or sweets, etc.). In contrast to this, pulp pain can be intermittent, from mild to unbearable, and appear spontaneously without an apparent stimulus.